High Rise Building: Vibration Control using Tuned Mass Damper - Lim , Vicheaka (Universiti Teknologi Petronas, 2013)
The availability of advance material, advance construction technology and powerful finite element analysis software have made modern tall building taller, slender and lighter which translate into dynamic force susceptibility. The main product of dynamic force is vibration in the building. The vibration causes discomfort to the occupants of the building and even damage the tall building to some extent. There are several method to mitigate this vibration problem. This project focus on using Tuned Mass Damper as the mitigation measure. The objective of this project is to apply the tuned mass damper characteristic onto a structural model of a building using finite element software in order to reduce its dynamic response and ultimately mitigate the vibration problem. The project cover the fundamental of structural dynamic, fundamental of tuned mass damper, dynamic analysis of a simple frame and a full frame structure and, finally, application of TMD on those structure. SAP2000 is used in this project as the main tool. A simple frame two storey 2D model known as Frame A and a full 3D model known as Frame B is used in this project for analysis. Preliminary dynamic analysis was done on Frame A using manual calculation and also using SAP2000. The result comparison between the two indicate that SAP2000 result is acceptable to use for analysis. Further time history analysis using periodic force with matching natural frequency applied on to the structure clearly shown the resonant effect. TMD was successfully design and integrated onto the structure in SAP2000 where the result show a reduction of structural dynamic response of Frame A and frame B.